Enduring tragedy the anguish of coping with survival : based on Stephen Ladislav Rajec's recollections of struggle to survive in Slovakia during WWII and his quest as a survivor in the USA - Rajec, Elizabeth Molnar (Delgen Press, 2019)
"Survivor's recollections of Herman Reitmann [Stephen Ladislav Rajec], about the tragic fate of his Jewish family, about his struggle as a forced laborer during World War II in Slovakia and about Stephen Ladislav Rajec's regained life as an immigrant in the USA.